Optimization of TIG welding parameters for tensile load testing on dissimilar material joints of galvanized steel (SGCC) and low carbon steel (SPCC-SD) - Basit, Arul; khoirudin, khoirudin; Sukarman, Sukarman; Cahyo, Tegar Dwi; Hidayat, Syahrul Taufik; Saputra, Ridhwan Shalahuddin; Ramadan, Trisa; Rahdiana, Nana (Politeknik Negeri Lhokseumawe, 2024)
Tungsten Inert Gas (TIG) welding uses a tungsten electrode and argon or helium gas for shielding. It offers excellent shielding, stable arc, adjustable heat input, minimal spattering, and attractive welds. Widely used in various industries, especially for thin materials like galvanized sheets, TIG welding can be challenging for dissimilar materials like galvanized steel and low-carbon steel due to their different melting points. Studying optimal welding parameters is crucial for success. This research focuses on TIG welding of SPCC-SD (JIS 3141) and SGCC (JIS 3302) materials with thicknesses of 0.6 mm and 0.8 mm. The electric current was varied at 45, 50, and 55 A, whereas the gas flow rate was varied at 12, 15, and 18 LPM. The weld bead diameter was varied as 5, 8, and 10 mm. Subsequently, the welded samples were subjected to tensile testing using a SHIMADZU AGS-X 10Kn STD E200V tensile testing machine. The data from the tensile tests were analysed using S/N ratio analysis and Analysis of Variance (ANOVA) with the assistance of the Minitab software. The results of the S/N ratio analysis indicated that the most optimal parameters were an electric current of 55 A, flow rate of 15 LPM, and weld bead diameter of 10 mm. Conversely, the ANOVA revealed that the weld bead diameter significantly influenced the tensile load in TIG welding of SPCC-SD (JIS 3141) with SGCC (JIS 3302) materials, accounting for up to 44.42% of the variation. Following the weld bead diameter, the flow rate and welding current contributed to 21.93% and 16.41%, respectively.